2018
DOI: 10.1080/08039488.2018.1424238
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between vitamin D and mania: correlations between serum vitamin D levels and disease activity

Abstract: Our results contribute to the idea that vitamin D deficiency and acute manic episode may have interactions with many pathways. Future trials may investigate this association with longer follow up. We recommend that serum vitamin D levels should be measured in patients with bipolar disorder especially in long term care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 26 publications
1
19
1
1
Order By: Relevance
“…Next control laboratory tests performed one month after the initial hospitalization showed a re-increase of these indicators, which could be attributed to the continuous use of psychoactive substances. Additionally, the patient was confirmed with significant hypovitaminosis D (9.99 ng / ml), which, according to the literature, may be associated with mood disorders, depression and bipolar disorder [ 21 , 22 ]. In addition, low vitamin D3 levels are a predictor of suicide attempts.…”
Section: Discussionmentioning
confidence: 98%
“…Next control laboratory tests performed one month after the initial hospitalization showed a re-increase of these indicators, which could be attributed to the continuous use of psychoactive substances. Additionally, the patient was confirmed with significant hypovitaminosis D (9.99 ng / ml), which, according to the literature, may be associated with mood disorders, depression and bipolar disorder [ 21 , 22 ]. In addition, low vitamin D3 levels are a predictor of suicide attempts.…”
Section: Discussionmentioning
confidence: 98%
“…Cependant, Altunsoy et al ont souligné que la dose neuroprotectrice de vitamine D n'était pas encore connue, et ce d'autant plus que le SNC serait capable de convertir la 25OHD en calcitriol et que le taux sérique de 25OHD pourrait retentir sur la synthèse de vitamine D active au niveau du cerveau. 39 Ceci soulève la question de l'étendue des effets positifs de la 25OHD sur le SNC.…”
Section: Discussionunclassified
“…Altunsoy et al [ 25 ], reported the serum levels of 25 (OH) vitamin D in healthy adults with a mean age of 37.58 years (23 male, 17 female) as 22.31 ± 8.8 ng/ml. Another study found that the median value of 25 (OH) vitamin D in 50 healthy adults with a mean age of 53.44 ± 8.4 22 years as 22 (6–40) ng/ml [ 26 ].…”
Section: Discussionmentioning
confidence: 99%